MODEL OF A CASCADE OF DIVERSION HYDROELECTRIC POWER PLANTS WITH FUZZY LOGIC CONTROLLER - L. Tolstikhina; D. Glashev (Вестник Северо-Кавказского федерального университета, 2022)
Diversion hydropower plants are one of the most environmentally friendly sources of energy, and improving the efficiency of water resources is an important task. The development of hydropower projects of this type is largely due to the technical and financial feasibility of implementation, which is very important for regions with mountainous terrain, large hydropower potential and a shortage of electric energy. The use of the MATLAB/Simulink simulation environment is possible to implement a model of a hydroelectric power station cascade with optimal use of riverflow. This allows you to determine the main parameters at the stage ofpre-project justification of the construction of a hydroelectric power station.